Knowledge, attitudes and behavior of consumers towards sustainability and ecological fashion - Ceylan, Özgür (Array, 2019)
The knowledge, attitudes and behavior of consumers towards sustainability and ecological fashion were explored through a survey of 476 participants and data were analyzed using descriptive statistics and correlation analysis. The attitude of participants towards sustainability was found to be positive. However, participants did not show positive behavior towards sustainability practices, meaning the positive attitude does not necessarily reflect on their behavior. Yet, participants who have positive attitudes towards environmental sustainability practices seem to reflect these attitudes relatively more toward their behavior. In addition, the knowledge level of participants was determined to be above the average in terms of ecological fashion. Their attitudes towards ecological fashion were also positive. Yet, this positive attitude, does not always reflect positively on behaviors. The results of this study provide a better understanding of the different factors that can influence consumer behavior towards sustainability, eco fashion and corresponding products, and thus will facilitate the implementation of relevant company strategies.